Collection of species like prawns, shrimps and other fishes - Mumbai Archive Project Team (Jio Institute, 2024)
The summer months of March to May mark another peak fishing season in Mumbai, especially for catching species like shrimp and prawns. As sea temperatures rise, these crustaceans become more active, attracting fishermen to coastal waters and estuaries where they are commonly found.